HARMONY IN DIVERSITY: A THEORETICAL PERSPECTIVE ON CONFLICT RESOLUTION IN INTERCULTURAL INTERACTIONS - Nor Hanim Mustafa; Nur Rasyidah Mohd Nordin (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This conceptual study explores the complex features of cross-cultural interaction and emphasises the development of a comprehensive framework to improve our understanding of cultural dynamics. Based on an extensive literature review, the study identifies conceptual inadequacies, particularly with regard to communication styles, conflict resolution, cultural intelligence, and adaptation. The conceptual framework presented here synthesises key concepts and theories from other disciplines to offer a cogent foundation for explaining the complexity of intercultural engagement. The framework emphasises the need for a thorough understanding of power dynamics, negotiation strategies, and cultural sensitivity. It serves as a road map for those trying to navigate the challenging terrain of cross-cultural encounter. Through comprehensive analysis of real-world examples and scenarios, the study illustrates the value of the proposed framework. It talks about the challenges posed by cultural variety and makes recommendations for fostering amicable and productive intercultural communication. This contribution strives to advance the field by offering a conceptual model that not only takes into account the particular difficulties of cultural connections but also incorporates contemporary thinking. The goal of this study is to give practitioners a comprehensive understanding of intercultural engagement, which will guide future research initiatives, and to assist them in establishing fruitful cross-cultural interactions in a variety of circumstances.